Using the analytic hierarchy process to elicit patient preference in the evaluation of first-line treatment of HER2-overexpressing metastatic breast cancer - Paula Medeiros do Valle; Cid Manso de Mello Vianna; Gabriela Bittencourt Gonzalez Mosegui; Idoaldo José de Lima; Magda Conceição Gomes Falcão Leal; Fabiano Saldanha Gomes de Oliveira (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2023)
Abstract Background The many combinations of chemotherapeutic agents and biologicals available in the Brazilian National Health System for the treatment of metastatic breast cancer require analysis that contribute to decision making. Objective The study's primary aim was to evaluate the first-line treatment of HER2- overexpressing metastatic breast cancer from the Brazilian Unified Health System perspective using multicriteria decision analysis (MCDA). Method The treatment options evaluated were (a) pertuzumab combined with trastuzumab and docetaxel, and (b) trastuzumab in combination with docetaxel. Using the hierarchical analytical method, medical oncologists compared the relevance of five predefined criteria: overall survival, response to treatment, adverse events, cost- effectiveness, and budget impact. Results The therapeutic scheme considered more appropriate by the model was pertuzumab combined with trastuzumab and docetaxel. The most sensitive criteria were adverse events, cost-effectiveness, and budget impact. The results suggest that the classification has a close relationship with the perspective of healthcare professionals participating in the questionnaire. Conclusion Defining the treatment of an incurable disease associated with a short survival time and high-cost treatment options necessitates complex decision-making. MCDA allows the weighting of criteria and considering criteria that would be difficult to measure in other methods, such as cost-effectiveness. These aspects differ from economic models and contribute to a broader evaluation of health decision-making.